Effects of local vibration on dynamic strength training - Drummond, M. D.; Couto, B. P.; Oliveira, M. P.; Szmuchrowski, L. A. (The Journal of Strength and Conditioning Research, 2021)
The study aim was to compare the chronic effects of maximal dynamic strength training with and without the addition of local vibration (LV) on maximal force generation and hypertrophy of the elbow flexor muscles in trained subjects. Twenty men were divided into 2 groups (conventional training [CT] group and vibration training [VT] group). The CT group performed conventional maximal dynamic strength training, and the VT group performed maximal dynamic strength training with mechanical vibrations (frequency of 26 Hz and amplitude of 6 mm). CT and VT groups performed 5 sets of 3-4 repetitions, with 2-minute rest intervals between sets. The subjects trained 3 times per week for 12 weeks. After the training period, the CT group presented a significant increase in the mean 1 repetition maximum (1RM) value in the elbow flexion exercise in the orthostatic position (EFO) (7.2 ± 1.5%) (p < 0.0001) and elbow flexion exercise using the Scott bench (EFSB) (6.3 ± 1.8%) (p < 0.0001). The VT group also showed significant increases in 1RM values in the EFO (6.87 ± 0.8%) (p < 0.0001) and EFSB (6.56 ± 1.4%) (p < 0.0001). The CT group presented a significant increase in the mean maximal voluntary isometric contraction (MVIC) value after the training period (8.2 ± 2.3%) (p < 0.0001). The VT group also showed a significant increase in the mean MVIC value after training (9.1 ± 2.4%) (p < 0.0001). After the training period, both groups presented a significant increase in the mean value of elbow flexor thickness (CT = 5.6 ± 3.5%, VT = 5.1 ± 2.8%) (p = 0.001). The increases in 1RM, MVIC, and muscle thickness were statically similar between groups. Therefore, the addition of LV does not represent an additional stimulus for individuals trained in dynamic maximal strength training.